2017
DOI: 10.1007/s00429-017-1579-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal density and proportion of interneurons in the associative, sensorimotor and limbic human striatum

Abstract: The striatum (caudate nucleus, putamen and nucleus accumbens) is the main input structure of the basal ganglia. It receives cortical projections from the vast majority of the cortex, as well as from other subcortical structures such as the thalamus and amygdala. Its role in planning, preparation and execution of voluntary movements is known to be fine-tuned by the interaction between projection neurons and interneurons. Since the 1990s, it has been accepted that the proportion of interneurons increases phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…17 We found that our neuronal nuclei samples contained approximately 85% MSNs and 15% interneurons; this is a higher proportion of interneurons than was recovered from single-cell analysis of rodent striatum 17 but consistent with counts made in humans. 53 A novel and relatively rare MSN type has been recently documented and variously described as eccentric SPNs, 16,17 Pcdh8-MSNs, 13 and D1H. 15 Both D1/D2 hybrids and D1-NUDAP neurons shared some characteristics with this novel cell type.…”
Section: Discussionmentioning
confidence: 94%
“…17 We found that our neuronal nuclei samples contained approximately 85% MSNs and 15% interneurons; this is a higher proportion of interneurons than was recovered from single-cell analysis of rodent striatum 17 but consistent with counts made in humans. 53 A novel and relatively rare MSN type has been recently documented and variously described as eccentric SPNs, 16,17 Pcdh8-MSNs, 13 and D1H. 15 Both D1/D2 hybrids and D1-NUDAP neurons shared some characteristics with this novel cell type.…”
Section: Discussionmentioning
confidence: 94%
“…In conclusion, numerical densities per volume, corrected for Z-axis shrinkage, were calculated with the following equation [51]:…”
Section: Stereological Analysis Of Striatal Neuron Densitiesmentioning
confidence: 99%
“…Genetically, it affects the 4th chromosomal gene; huntingtin (HTT) protein mutation and misfolding. The main area of the brain is affection in caudate; putamen nucleous; globus pallidus; and nucleus accumbens leads to cause the atrophy of brain via the neurodegenerative process [32,72]. The microscopical observation revealed that small spiny neurons of the caudate and putamen cause the astrocytosis.…”
Section: Role Of Lpo In Huntington Diseasementioning
confidence: 99%
“…The chronic event of cellular neurodegenerative process enhances the neuronal oxidative stress with an accumulation of free radicals and LPO process [73]. During the early stage of LPO process; neuronal cells losses the cell contents; shrinkage of caudate nucleolus; shrinkage and dilatation of the anterior horns of lateral ventricles [45,72]. Moreover, LPO process enhances the alteration of various neurotransmitters such as a gamma aminobutyric acid (GABA); acetylcholine; and substance P [74,75].…”
Section: Role Of Lpo In Huntington Diseasementioning
confidence: 99%